Evaluation of YouTube videos addressing thoracoscopic sympathectomy using the LAP-VEGaS guidelines - Adorisio, Ottavio; Davoli, Enrico; De Peppo, Francesco (Frontiers in Surgery, 2023)
Introduction The study aims to evaluate the quality of videos addressing thoracoscopic sympathectomy on YouTube® using the LAParoscopic surgery Video Educational GuidelineS (LAP-VEGaS) criteria. Methods YouTube was searched using the following keyword: “thoracoscopic sympathectomy” on August 22, 2021. The first 50 videos were analyzed and classified for baseline characteristics and conformity to the LAP-VEGaS checklist. Results Duration ranged from 19 s to 22 min. The mean number of likes was 14.8 (range 0–80). The mean number of dislikes was 2.5 (range 0–14). The mean number of comments was 8.5 (range 0–67). Nineteen videos did not meet our criteria and were excluded. Regarding the remaining 31 videos, none contained all 16 points of the LAP-VEGaS essential checklist (mean 5.4 points, range 2–14 points), with almost all neglecting preoperative information and outcomes. The mean percentage of conformity was 37% (range 12%–93%). The most viewed videos were not associated with higher conformity to LAP-VEGaS criteria showing only 4/16 points (25%). Conclusions The quality of videos addressing TS on YouTube®, based on the LAP-VEGaS checklist may be considered not acceptable. Experienced surgeons and surgeons in trainees should be aware of this when using it as a learning resource in their clinical practice.